Have we designed the way for Bologna Process? - Yelo Díaz, Soledad; Domínguez Alcarazo, Carlos (Avances en Supervisión Educativa, 2009)
The educational change, settled by the European Space of High Education for Spain in 2010, is based on the development of a competential work, a needed methodological change, a curricular and physical movement and, also, the conception of Education as a permanent process. It proposes teaching procedures that imply more dynamic, diverse and guided didactics. The latest legislative reformations for Primary and Secondary Education shows these aspects in a way which results will be the immediate future. Our secondary scholars are the reserve of students that will conclude the change that the Bologna Plan means. Will they be ready for it? A short debriefing about the key points of the University reformation that has begun are, as a reflection, the image to which the basic educational levels must respond.